Correction: Yulangsan polysaccharide improves redox homeostasis and immune impairment in d-galactose-induced mimetic aging. Issue 12 (21st May 2021) - Doan, Van Minh; Chen, Chunxia; Lin, Xing; Nguyen, Van Phuc; Nong, Zhihuan; Li, Weisi; Chen, Qingquan; Ming, Jianjun; Xie, Qiuqiao; Huang, Renbin
Abstract : Correction for 'Yulangsan polysaccharide improves redox homeostasis and immune impairment in d -galactose-induced mimetic aging' by Van Minh Doan et al., Food Funct., 2015, 6, 1712–1718, DOI: ; 10.1039/C5FO00238A .